The La carga de las mochilas provoca trastornos posturales en alumnos de primaria - Hasbiah Hasbiah; Hendrik Hendrik; Melvi S. Tandi; Supartina Hakim; Andi Halimah; Arpandjam’an Arpandjam’an (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Objectives: In children between 10 and 15 years, postural disorders have been diagnosed. If the disease is not treated, it will worsen with age. This can affect cardiopulmonary function, limit mobility, and cause structural problems. Early detection of postural disorders is crucial to prevent any abnormalities and injuries from worsening. The purpose of this study was to analyze the impact of school bag or backpack loads on students with postural disorders at Paccerakkang Inpres Elementary School.  Method: This cross-sectional research uses observational research methods. They used observation sheets and data collected by direct measurement. The sample used was 75 primary school students from grades 1 to 3 who met the inclusion criteria of the sample size formula. The samples were gathered using simple random sampling. The study was conducted in 2023 between April and July. Results: It was discovered through descriptive analysis that the pupils' seating arrangements were not ergonomic. While some students carried bags that weighed over 10% of their body weight, others carried bags that weighed less than 10%. Compared with normal posture, there were more deviant postures. The prevalence of posture problems with the sitting position of elementary school children while studying did not have a significant relationship, according to the chi-square analysis (p > 0.358). The relationship between postural abnormalities and bag load was quite large (p < 0.020). Conclusion: Bag load impacts the prevalence of postural abnormalities in elementary school students at Inpres Paccerakkang.